Fraud and Whistleblowing Intention: Organizational Justice Perspective - Ni Wayan Rustiarini; Luh Komang Merawati (Riset Akuntansi dan Keuangan Indonesia)
Whistleblowing is considered as an effective control mechanism for detecting fraud. One of the factors that influence individuals to do whistleblowing is organizational justice. However, research on the justice theory and whistleblowing is still limited. This study aims to investigate the role of distributive justice, procedural justice, and interactional justice on whistleblowing intention. This study uses an experimental laboratory method. The subjects were 124 accounting employees in the private and public sectors. The findings show that the employee who experience fair organizational justice (distributive, procedural, and interactional) have higher whistleblowing intentions than employees in unfair conditions. This study also reveals that does no whistleblowing intention difference between private and public employees.